Challenges and opportunities in bringing non-HLA antibody testing for post-transplant monitoring - Philogene, Mary Carmelle; Tchoukina, Inna; Gimferrer, Idoia (Frontiers in Transplantation, 2025)
Evidence for the contribution of non-HLA antibodies on long-term allograft outcome was suggested in early studies by Paul Terasaki and colleagues who showed worse 10-year allograft outcome in HLA identical kidney transplant recipients with a positive panel reactive antibody (PRA) as determined by the micro cytotoxicity assay, in which cells express other targets beside HLA. More recent reports have shown worse graft outcome when antibodies against non-HLA antigens were detected with HLA-donor specific antibodies (HLA-DSA), and even suggest that non-HLA antibodies may serve as precursor to development of HLA antibodies. Unfortunately, the recent studies lack reproducibility, which then leads to skepticism as to the relevance of non-HLA antibody in transplantation outcome. Consequently, routine testing for non-HLA antibody along with monitoring of HLA-DSA as part of a post-transplant immune surveillance protocol is not standard practice. The Sensitization in Transplantation: Assessment of Risk (STAR) workgroup summarized the current literature on this topic, citing differences in cohort characteristics, variability in study design, selection of sample and timepoints for testing and variability in the assays used to detect non-HLA antibodies, as reasons that impact the accurate assessment on the relevance of non-HLA antibodies. However, correlation between test results and outcome can only be determined if the assay in question is detecting the correct analyte. Therefore, here we will make the case for a plan that requires a systematic validation of high-throughput bead-based assays, to include appropriate sequence selection for non-HLA antigenic targets and quality control metrics as a first step to solving this puzzle.